Biology of sexual differentiation - De Marinis, Laura; Barbarino, Antonio; Serra, Angelo (Medicina e Morale, 2024)
Recent advances in genetics, experimental endocrinology, molecular biology and biochemistry have provided new insights into the mechanisms and processes of sexual differentiation (DS). Some of these new findings have made it possible to elucidate particular clinical syndromes in their pathogenesis, while others have helped to determine where, how and when the normal process of DS can be altered.